Stereotypically thinking: Norms for stereotypical gender nouns in Polish and English. - Katarzyna Jankowiak; Marcin Naranowicz; Anna Skałba; Dariusz Drążkowski; Joanna Pawelczyk (PLoS ONE)
The present contribution provides norms for a database of Polish (a grammatical gender language) and English (a natural gender language) stereotypical gender and neutral nouns. A total of 317 participants rated the degree of stereotypically feminine and masculine features when presented with 240 nouns in each language. The stimuli were highly controlled for a number of psycholinguistic variables, including word frequency, the number of letters and syllables, age of acquisition, concreteness, valence, and arousal. The results of the ratings revealed that gender stereotypical features were observed in both language systems, thus suggesting that single words that do not explicitly reference any male or female characteristics can activate stereotypically feminine and masculine schemas, regardless of grammatical gender. Furthermore, the results suggested a stronger internalization of gender stereotypes among female relative to male participants as well as among sex-typed individuals, therefore pointing to the crucial role of gender and gender schema in how sensitive individuals are to gender stereotypical attributes. The norms reported in the present article aim to broaden researchers' stimulus choices and allow for consistency across different laboratories and research projects on gender stereotype processing. The adaptation of this database to other languages or cultures could also enable a cross-cultural comparison of empirical findings on stereotype processing.